(Effectiveness Of Online Learning During The Covid-19 Pandemi In Basic Course Subjects At State Vocational High School 3, Solok City - Asnita, Asnita; Yulastri, Asmar (Universitas Negeri Padang, 2023)
The background of this research is that most of the students are less active and enthusiastic in carrying out online learning, the lack of outreach by teachers to students in using online learning media, and the lack of teacher creativity in designing and managing online learning. This study aims to: Know and describe the effectiveness of online learning during the Covid-19 pandemic in Basic Culinary Subjects in Class XI Culinary Planning at SMKN 3 Kota Solok in the 2020/2021 Academic Year. This type of research uses an ex post facto research method with an exploratory descriptive approach. The population in this study were all students of Class XI Catering at SMKN 3 Kota Solok for the 2021/2022 academic year with a total of 43 students. The sample in this study used a saturated sampling technique. The sample in this study were all 43 students of class XI Culinary Planning who had attended Basic Culinary lessons in class X SMKN 3 Kota Solok. Data collection was carried out by distributing questionnaires via the Google form which were distributed directly to students in the WhatsApp group and measured using a Likert scale which has been tested for validity and reliability. Analysis of the data used is descriptive analysis with a tendency to test the level of effectiveness. The results of research on the effectiveness of online learning during the Covid-19 pandemic in Basic Food subjects in class XI SMKN 3 Solok City, out of 43 respondents, it was found that 6 people (13.9%) were in the very effective category, 7 people (16.2%) were in the very effective category. effective, in the quite effective category 18 people (42%), in the ineffective category 9 people (21%), and in the very ineffective category 3 people (6.9%). The highest number of frequencies are in the quite effective category with 18 respondents (42%) and it can be concluded that the Effectiveness of Online Learning during the Covid-19 Pandemic in Basic Culinary Subjects in Class XI SMKN 3 Kota Solok is in the category of quite effective.